Manganese Inhalation as a Parkinson Disease Model - José Luis Ordoñez-Librado; Verónica Anaya-Martínez; Ana Luisa Gutierrez-Valdez; Laura Colín-Barenque; Enrique Montiel-Flores; Maria Rosa Avila-Costa (Parkinson's Disease)
The present study examines the effects of divalent and trivalent Manganese (Mn2+/Mn3+) mixture inhalation on mice to obtain a novel animal model of Parkinson disease (PD) inducing bilateral and progressive dopaminergic cell death, correlate those alterations with motor disturbances, and determine whether L-DOPA treatment improves the behavior, to ensure that the alterations are of dopaminergic origin. CD-1 male mice inhaled a mixture of Manganese chloride and Manganese acetate, one hour twice a week for five months. Before Mn exposure, animals were trained to perform motor function tests and were evaluated each week after the exposure. By the end of Mn exposure, 10 mice were orally treated with 7.5 mg/kg L-DOPA. After 5 months of Mn mixture inhalation, striatal dopamine content decreased 71%, the SNc showed important reduction in the number of TH-immunopositive neurons, mice developed akinesia, postural instability, and action tremor; these motor alterations were reverted with L-DOPA treatment. Our data provide evidence that Mn2+/Mn3+ mixture inhalation produces similar morphological, neurochemical, and behavioral alterations to those observed in PD providing a useful experimental model for the study of this neurodegenerative disease.